Perancangan Identitas Visual sebagai Rebranding Taman Hutan Raya Lempung Surabaya - Azzah, Zafirah Lifia; Arifianto, Pungky Febi; Setiawan, Bayu (VISA: Journal of Vision and Ideas, 2025)
Taman Hutan Raya Lempung is one of the botanical forest parks in Surabaya, East Java. The purpose of the construction of Taman Hutan Raya Lempung is to create a green space in Surabaya. In addition, the park is also used as a tourist destination. However, many people in Surabaya and its surroundings still do not recognize or know about Taman Hutan Raya Lempung. The purpose of the project is to design a visual identity as a rebranding for Taman Hutan Raya Lempung to increase the awareness of the people of Surabya and its surroundings about the tourist destination. This research uses qualitative and quantitative methods through primary data such as interviews, observations, and questionnaires also secondary data through a literature review. The data analysis techniques used are 5W+1H analysis and TOWS matrix analysis.